Learn GarageBand Mac video training - Miller, Derek K.; Garay, Paul.; Kaye, Michael; Safari eBooks ([S.l.] : Peachpit Press, 2010)
"Anyone can rock out with GarageBand '08! Create songs with easy-to-customize pre-made music loops, all the way up to pro-grade recording tools for the working musician, GarageBand has you covered. Our video training helps you get the most out of the music program that comes with every new Mac. Watch us show you how to make a song that would have needed a million-dollar recording studio just a few years ago. Turn your passion into a podcast and share it with the world, with better sound than any radio station. Finally, burn your mastered recordings to disc, or export them as MP3's. It's never been easier!"--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed Jan. 6, 2011).
Keywords: GarageBand (Computer file); Digital audio editors; Electronic books